Hydrometallurgical Recovery of Tin from Waste-Printed Circuit Boards - Dimitrios Vlasopoulos; Paschalis Oustadakis; Emmanouella Remoundaki; Styliani Agatzini-Leonardou (Materials Proceedings)
This study presents a hydrometallurgical process for the leaching and recovery of tin from waste-printed circuit boards (wPCBs). The process aims to separate and recover tin from filter dust produced during the crushing of wPCBs in a recycling facility. The separation of the metallic and non-metallic fractions was carried out by gravimetric separation. The metallic fraction consisted mainly of Cu (23.8%), Fe (17.8%), Sn (12.7%), Pb (6.3%), and Zn (3.4%). During the leaching tests, the effects of (a) HCl concentration (2, 4, 6 M), (b) pulp density (0.1, 0.2, 0.3 g/mL), and (c) the addition of NaCl (no addition, 1 M, 3 M) were investigated. All tests were conducted at an ambient temperature without agitation. A leaching efficiency of 78.2% was obtained during leaching with 6 M HCl and 0.3 g/mL pulp density, while 94.8% of tin was leached under the same conditions with the addition of 3 M NaCl. Tin was recovered from the pregnant solution by addition of 2 M NaOH at pH = 3.0, with an efficiency of 97.4%. The precipitate, despite being amorphous, was easily filtered and it consisted of 64.7% Sn and less than 2% of impurities. The proposed process consists of a leaching stage with 6 M HCl, 3 M NaCl, 0.3 g/mL pulp density, and a contact time of 24 h, and a recovery stage by chemical precipitation at pH = 3.0. The total tin recovery of the suggested process was 92.3%.